2005
DOI: 10.1074/jbc.m409596200
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin F2α-mediated Activation of Apoptotic Signaling Cascades in the Corpus Luteum during Apoptosis

Abstract: Prostaglandin F 2␣ (PGF 2␣ ) acting via a G protein-coupled receptor has been shown to induce apoptosis in the corpus luteum of many species. Studies were carried out to characterize changes in the apoptotic signaling cascade(s) culminating in luteal tissue apoptosis during PGF 2␣ -induced luteolysis in the bovine species in which initiation of apoptosis was demonstrable at 18 h after exogenous PGF 2␣ treatment. An analysis of intrinsic arm of apoptotic signaling cascade elements revealed that PGF 2␣ injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 61 publications
5
67
0
Order By: Relevance
“…It has been shown that PGF 2a interacts with its G-protein-coupled receptor to increase the ratio of Bax to Bcl2, which are closely associated with the elevation of the expression of caspase9 and caspase3 (Yadav et al 2005). The mechanism by which Slit/Robo exerts this effect on apoptosis is unclear; however, the deleted in colorectal cancer (DCC) pathway may play a role in this progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that PGF 2a interacts with its G-protein-coupled receptor to increase the ratio of Bax to Bcl2, which are closely associated with the elevation of the expression of caspase9 and caspase3 (Yadav et al 2005). The mechanism by which Slit/Robo exerts this effect on apoptosis is unclear; however, the deleted in colorectal cancer (DCC) pathway may play a role in this progression.…”
Section: Discussionmentioning
confidence: 99%
“…The functional phase is associated with a marked decrease in progesterone production, which is followed by the structural phase in which the luteal cells die through programmed cell death (Hernandez et al 2011). ligands and death receptors (Kuranaga et al 1999, Roughton et al 1999, Sartorius et al 2001. Several signals have been implicated in the induction of the apoptosis of luteal cells, including prostaglandin F 2a (PGF 2a ), progesterone, prolactin, and Fas ligand (FasL; Bowen et al 1996, Roughton et al 1999, Gaytan et al 2000, Kuranaga et al 2000, Taniguchi et al 2002, Carambula et al 2003, Yadav et al 2005. It has been reported that PGF 2a interacts with its G-proteincoupled receptor; this interaction increases the ratio of Bax to Bcl2, thus elevating the protein levels and activity of caspase9 and caspase3 (Yadav et al 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though a comprehensive study of the role of BID in cell death within the ovary using knockout mice is yet to be published, several studies have hinted at important roles in follicular atresia and corpora lutea regression (Yadav et al 2005, Goyeneche et al 2006, Sai et al 2011, Paulose et al 2012, Craig et al 2013. More than 99% of the growing follicles in the ovary are destined for atresia, which is usually first evident by apoptosis of the granulosa cells.…”
Section: Bh3 Interacting Domain Death Agonistmentioning
confidence: 99%
“…The authors implied that this reduction in BID expression might have been due to its cleavage to the active tBID form, but tBID expression itself was not evaluated and active caspase-8 could not be detected (Goyeneche et al 2006). Another study clearly showed increased expression of FAS and FASL increased caspase-8 activity, BID cleavage to tBID and increased caspase-3 and -9 cleavage during PGF2 a-induced bovine luteal tissue apoptosis (Yadav et al 2005). Indeed, a potential role for BID in triggering luteal cell apoptosis during normal cycling is supported by many studies carried out in rodents, cattle and humans showing FAS signalling and caspase-8 activation during luteolysis (Quirk et al 1995, Sakamaki et al 1997, Kuranaga et al 2000a,b, Taniguchi et al 2002, Carambula et al 2003.…”
Section: Bh3 Interacting Domain Death Agonistmentioning
confidence: 99%